Governance networks for agroecology transitions in rural Europe - Gava, Oriana; Vanni, Francesco; Schwarz, Gerald; Guisepelli, Emmanuel; Vincent, Audrey; Prazan, Jaroslav; Weisshaidinger, Rainer; Frick, Rebekka; Hrabalová, Andrea; Carolus, Johannes; Yoldi, Uxue Iragui; Pyysiäinen, Jarkko; et al. (Pergamon Press, 2025)
Governance networks, made of diversified and multidisciplinary actors, have a prominent role in the development and implementation of actions for agri-food system transformation that foster both farm-level and societal change, as in the case of agroecology transitions. This article aims at delivering a typology of governance networks, building on evidence from across Europe. By adopting a governance network theory perspective, a multiple case study is developed through participatory research, by characterising the emerging governance networks from transition actions at different levels in the pathway towards agroecological redesign. Three types of governance networks are identified. Adoption networks develop from early-stage actions in the agroecology transition pathway, to facilitate the shift from conventional to more sustainable farming practices. Positioning networks emerge from actions to create a demand for agroecologically produced food, through the development of marketing strategies and the creation of market channels. Amplification networks are the closest to agroecological redesign, originating from actions structured towards participatory planning and the development and reinforcement of diversity and transdisciplinarity. Advisory services play a key role in all three types, by fostering knowledge diffusion and exchange, as well as by developing trust among farmers and encouraging cooperation, including conflict management. The role of advisory services for agroecology could be strengthened further through targeted policy. Measures to sustain multi-actor cooperation have the potential to create these conditions by developing and exploiting synergies between and within value chains, and with other relevant actors, including consumers.
Keywords: transition actions; agroecology transition; social network analysis; content analysis; multi-method; mixed-methods; governance network theory